THE CHANGE OF ACCOUNT RECEIVABLE, EQUITY, AND LEVERAGE ON CURRENT RATIO IN MINING FIRMS - Maulana, Rizal Achmad; Widhianningrum, Purweni (Journal of Accounting and Business Education, 2016)
This study aims to analyzes the effect of receivables turnover, working capital turnover and debtÂ  ratio to current ratio in mining company. The population in this study are all mining companies listed on the Indonesia Stock Exchange during the period 2011 through 2014, which amounted to 39 companies. The sampling technique in this study used purposive sampling, as many as 14 companies. This study uses multiple linear regression analysis. The results showed that receivable turnover and working capital turnover does not affect the current ratio. While debt ratio significantly influence a companys current ratio. This proves that with high debt ratio, the creditors still believe mining companies in Indonesia. The increase in business scale through volume production capacity and sales are considered able to provide additional corporate earnings impact on the decrease current ratio.Keywords: receivables turnover, working capital turnover, debt ratio, current ratio, mining company.